Analysis of factors affecting tax avoidance and firm value - Mayke Kristika Antony; Gunasti Hudiwinarsih (The Indonesian Accounting Review, 2018)
The aim of this study is to examine and analyze factors that influence tax avoidance and firm value. The independent variables used in this study are audit quality and profitability, while the dependent variable is firm value, and the intervening variable is tax avoidance. The sample used in this study is banking sector companies in Southeast Asia that listed in www.orbis.bvdinfo.com for the period 2014-2016. The technique of data analysis used in this study is multiple regression analysis with SPSS 22.0 For Windows Program and path analysis. The results of this study show that audit quality has no influence on tax avoidance, but profitability has influence to tax avoidance. Audit quality, profitability, and tax avoidance have influence on firm value, while tax avoidance cannot mediate the influence of audit quality and profitability on firm value.Â